IMPLEMENTASI MEDIA PEMBELAJARAN BUSA (BUKU SAKU) BERBASIS MIND MAPPING PADA PEMBELAJARAN IPA MATERI SIKLUS AIR KELAS V SDN JATIURIP I KABUPATEN PROBOLINGGO - Maulidza Wijayanti; Ludfi Arya Wardana; Shofia Hattarina (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the preparation, implementation and assessment of the implementation of mind mapping-based pocketbook learning media in science lessons on water cycle material for class V SDN Jatiurip I, Probolinggo district. This research uses a qualitative method, by exploring research data in the form of descriptive or words that describe all the data findings that have been found while in the field. Based on the results of the research data, it is clear that the class V teacher prepares for science lessons by making complete and systematic lesson plans and preparing learning media that are relevant to the learning material, namely using mind mapping-based pocketbooks. The implementation of science learning using the pocketbook media has systematic stages, in accordance with the lesson plan that has been made by the teacher. Science learning assessment with pocketbook media can improve student achievement.